Association of interleukin-1 and interleukin-6 levels in lateralized temporal epilepsy patients - Varoglu, Asuman Orhan; Avarisli, Aysenur; Keskin, Havva; Erman, Hayriye (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the clinical significance of interleukin-1 and interleukin-6 in the development of lateralized temporal epilepsy. Method: The prospective study was conducted from January to April of 2022 at the Neurology Department of Training and Research Hospital, Istanbul Medeniyet University, Turkey, and comprised patients with lateralized temporal epilepsy aged 18-86 years who were in the interictal period in group A and healthy controls in group B. The levels of interleukin-1 and interleukin-6 of patients in both groups were compared. Data was analysed using SPSS 25. Results: Of the 92 subjects, 60(65.2%) were in group A; 35(58.3%) were males and 25(41.7%) were females with a median age of 37.5 years (interquartile range: 2.2-42.7 years). There were 32(34.8%) subjects in group B; 19(40.6%) females and 13(40.6%) males with a median age of 40.5 years (interquartile range: 25-50 years) (p>0.05). Within group A, 41(68.3%) patients had left-sided epilepsy and 19(31.7%) had right-sided epilepsy (p<0.001). Both interleukin-1 and interleukin-6 levels were lower in group A than in group B (p<0.001). Both interleukin levels did not significantly differ between right and left-lateralised temporal seizures (p=0.44). In the left-lateralized temporal seizures, interleukin-1 levels correlated with epilepsy duration (p<0.006), lower onset age (p<0.050), and presence of prenatal risk (p<0.028). Interleukin-1 and interleukin-6 levels were positively correlated with each other for lateralized temporal epileptic hemispheres (p<0.001). Conclusion: Interleukin-1 level was correlated with epilepsy duration, lower onset age, and presence of prenatal risk in the left-lateralized temporal epilepsy. Key Words: Focal epilepsy, Partial epilepsy, Lateralisation, Prognosis, Interleukin-1, Interleukin-6, Cytokine.